ANALISA RESETTING OVER CURRENT RELAY DAN GROUND FAULT RELAY PADA TRAFO 60 MVA 150/20 kV DAN PENYULANG 20 kV GARDU INDUK PADANG SAMBIAN - Gunawan, Indra; Rinas, Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM, 2018)
Electricity energy needs in Bali have increased annually by 135,2 GWh, as a result, the State-Owned Electrcity Company (PLN) is being required to add new power plants or the addition of transformer to serve load side fedeers. New transformer have been added to Padang Sambian substation and the reconfiguration of Padang Sambian feeders. The reconfiguration causes the feeder impedance value to change, thus affecting the protection system such as Over Current Relay (OCR) and Ground Fault Relay (GFR). Calculation of current setting and OCR and GFR relay work time can minimize the interference that occurs. The amount of short circuit current that occurs in Padang Sambian fedeers was calculated to determine the value of relay settings. The result of the analysis showed that the OCR current setting value for the incoming side of 0,91 A with Time Multiplier Setting (TMS) was 0,2 SI and OCR on the outgoing side of 2,063 A with TMS of 0,161 SI. The value of current setting for the incoming GFR was 0,01 A with TMS of 0,27 SI and the setting value of the GFR current on the outgoing side was 0,16 A with TMS of 0,106 SI. The result of Electrical Power System Analysis (ETAP) simulation obtained an OCR and GFR coordination curve that did not intersect the Time-Curve Current (TCC) characteristic. This shows that coordination runs well and meets sensitivity, reliability, selectivity and speed requirements.